Influence of wood storage time in the paper properties of Eucalyptus globulus - Pereira, M. (2013)
In this work we studied the effect of moisture and chip pile storage time of Eucalyptus globulus wood, regarding the impact in kraft cooking and papermaking. Experimentally, chip samples were collected with different storage times (0, 15, 30, 60 and 90 days) from two distinct piles (wet and dry). The cooked chips after disintegration, screening and washing were submitted to a bleaching stage, in ECF sequence following five stages (D0E1D1E2D2). The pulps were beaten in a PFI mill at 1000, 2000 and 3000 revolutions. For the cooking results we observed higher yield and lower alkali consumption for the wet pile chips and lower storage time (15 days). The results showed that storage time is a significant factor (ANOVA results) for almost paper properties studied and influenced mainly the internal fibre links. For what paper properties are concerned, the difference between piles isn’t so evident, the major differences are observed for the lower storage time (15 days).